TRAINERS OF SOCCER: AN ASSAY BY MEANS OF SOME DIFFICULTIES IN THE PRODUCTIVITY OF THESE PROFESSIONALS (Fiep Bulletin - online, 2015)
The present subject has the intention to present information concerning the important function played for the soccer trainer, being presented factors that demonstrate to its yearnings and the reality where this if inserts. It still brings some situations that involve the Porting Clubs and its directions that constantly are come across with problems in the structure and the organizacional planning, intervening directly with the routine of the trainers. We search with this study, to quantify aspects important for the profession of Trainer, being intent to be optimizing the productivity of this professional, whose information will be able to contribute in the construction of new strategies that will facilitate the strategical organization aiming at to contemplate the objectives of this professional.
Keywords: Trainers; Soccer; Organizacional Planning